Corinth in contrast : studies in inequality - Friesen, Steven J.; James, Sarah A.; Schowalter, Daniel N., 1957- (Supplements to Novum Testamentum, 2014)
In Corinth in Contrast, archaeologists, historians, art historians, classicists, and New Testament scholars examine the stratified nature of social, economic, political, and religious interactions in the city of Corinth from the Hellenistic period to Late Antiquity.